Variations in policies for accessing elective musculoskeletal procedures in the English National Health Service: A documentary analysis. Issue 3 (July 2022) - Rooshenas, Leila; Ijaz, Sharea; Richards, Alison; Realpe, Alba; Savovic, Jelena; Jones, Tim; Hollingworth, William; L Donovan, Jenny
Objective: The overall aim of this study was to investigate how commissioning policies for accessing clinical procedures compare in the context of the English National Health Service. Our primary objective was to compare policy wording and categorise any variations identified. Our secondary objective was to explore how any points of variation relate to national guidance. Methods: This study entailed documentary analysis of commissioning policies that stipulated criteria for accessing eight elective musculoskeletal procedures. For each procedure, we retrieved policies held by regions with higher and lower rates of clinical activity relative to the national average. Policies were subjected to content and thematic analysis, using constant comparison techniques . Matrices and descriptive reports were used to compare themes across policies for each procedure and derive categories of variation that arose across two or more procedures. National guidance relating to each procedure were identified and scrutinised, to explore whether these provided context for explaining the policy variations. Results: Thirty-five policy documents held by 14 geographic regions were included in the analysis. Policies either focused on a single procedure/treatment or covered several procedures/treatments in an all-encompassing document. All policies stipulated criteria that needed to be fulfilled prior to accessing treatment, but there were inconsistences in the evidence cited. Policies varied in recurring ways, with respect to specification of non-surgical treatments and management, requirements around time spent using non-surgical approaches, diagnostic requirements, requirements around symptom severity and disease progression, and use of language, in the form of terms and phrases ('threshold modifiers') which could open up or restrict access to care. National guidance was identified for seven of the procedures, but this guidance did not specify criteria for accessing the procedures in question, making direct comparisons with regional policies difficult. Conclusions: This, to our knowledge, is the first study to identify recurring ways in which policies for accessing treatment can vary within a single-payer system with universal coverage. The findings raise questions around whether formulation of commissioning policies should receive more central support to promote greater consistency – especially where evidence is uncertain, variable or lacking.